2018
DOI: 10.1002/uog.17466
|View full text |Cite
|
Sign up to set email alerts
|

Effect of change in posture on maternal functional hemodynamics at 35–37 weeks' gestation

Abstract: Paradoxically, in late third-trimester normal pregnancy, both change from the supine to a sitting position and passive leg raising may result in an increase in preload with a consequent increase in cardiac and stroke volume indices and a decrease in total peripheral resistance index. In pregnancies that develop PE or GH, the effects of postural change on cardiovascular parameters are similar but less marked than in normotensive pregnancies. Copyright © 2017 ISUOG. Published by John Wiley & Sons Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 27 publications
(28 reference statements)
0
9
0
Order By: Relevance
“…Cardiovascular response to PLR has been studied in the second half of singleton pregnancies by Vårtun et al; PLR led to a nonsignificant increase in SV from 20 +0 to 31 +6 weeks compared with baseline, whereas CO significantly decreases after 24 +0 weeks. Similarly, Guy et al recently demonstrated that PLR results in an increase in preload with a consequent increase in cardiac index and SI and a decrease in SVRI in 2764 normotensive women with singleton pregnancy at 35‐37 weeks’ gestation . By means of ICG we investigated hemodynamic response to PLR in healthy pregnant women during their twin pregnancies; these women seemed to be unable to respond to auto‐fluid challenge by increasing SV.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Cardiovascular response to PLR has been studied in the second half of singleton pregnancies by Vårtun et al; PLR led to a nonsignificant increase in SV from 20 +0 to 31 +6 weeks compared with baseline, whereas CO significantly decreases after 24 +0 weeks. Similarly, Guy et al recently demonstrated that PLR results in an increase in preload with a consequent increase in cardiac index and SI and a decrease in SVRI in 2764 normotensive women with singleton pregnancy at 35‐37 weeks’ gestation . By means of ICG we investigated hemodynamic response to PLR in healthy pregnant women during their twin pregnancies; these women seemed to be unable to respond to auto‐fluid challenge by increasing SV.…”
Section: Discussionmentioning
confidence: 87%
“…Although a reduction in myocardial contractility might represent one of the underlying mechanisms leading to myocardial inability to increase SV in response to PLR, compromised venous return due to caval compression and fluid shifts, including positioning of breast tissue, with the postural change could be another reason for the lack of positive response to PLR, as well as the small sample size. Indeed, Guy et al demonstrated a significant increase of only 3% in cardiac index and SI with PLR starting from the left lateral decubitus in 2764 singleton pregnancies near term In contrast, Liang et al reported no difference starting from a semi‐recumbent position in 53 singleton pregnancies in the second and third trimester …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, more emphasis has been put on the dynamic assessment of cardiovascular function (functional hemodynamics) rather than on the static measurements [1217]. Passive leg raising (PLR), a maneuver that consists of passively lifting the lower limbs from the horizontal plane up to 45°, has been used as an endogenous fluid challenge test as it leads to a certain amount of blood volume being auto-transfused into the central circulation, which subsequently can be expected to increase the cardiac output by Frank–Starling mechanism [18].…”
Section: Introductionmentioning
confidence: 99%